Stability Assessment of Rock Slopes in the Former Quarry of Wojciech Bednarski Park in Kraków—A Case Study - Malwina Kolano; Marek Cała; Agnieszka Stopkowicz; Piotr Olchowy; Marek Wendorff (Applied Sciences, 2025)
This study presents a stability assessment of rock slopes, considering the joint systems of the rock walls of Wojciech Bednarski Park. Special emphasis was placed on analysing the orientation and infill characteristics of the identified joint sets. Based on archival data and newly conducted geological surveys, stability calculations were performed for eight representative cross-sections corresponding to designated sectors. Numerical analyses were conducted using a finite element method (FEM) programme, based on the actual structure of the rock mass, specifically its discontinuities. This ensured a reliable reflection of the real conditions governing the slope instability mechanisms. Factors of safety were estimated with the Shear Strength Reduction Technique. The results indicate that slope failure is highly unlikely in Sectors 1 and 2 (FS > 1.50), unlikely but not fully meeting the safety criteria in Sector 3 (FS < 1.50), and highly probable in Sectors 4 and 6 (FS << 1.00), where unstable rock blocks and deeper structural slides are anticipated. In Sector 5, failure is considered probable (FS < 1.30) due to rockfalls, unstable blocks, and creeping weathered cover. For Sectors 7 and 8, assuming debris cover above the rock walls, failure is unlikely (FS > 1.50). In contrast, under the assumption of weathered material, it becomes probable in Sector 7 (FS < 1.30), and remains unlikely in Sector 8 (FS > 1.50). Due to the necessity of adopting several modelling assumptions, the results should be interpreted primarily in qualitative terms. The outcomes of this research provide a critical basis for assessing the stability of rock slopes within Wojciech Bednarski Park and support decision-making processes related to its planned revitalisation.